Participatory Action For and Through Ecological Integrity: Toroidality as a Circular Design Model - Yurt, Canberk; Deniz, Deniz (ITB Journal Publisher, DRPM ITB, 2025)
The ecological crisis corrupts natural cycles, damages networks of organisms, and disrupts the ecosystem equilibrium. In response to the ecological crisis, the concept of circularity proposes reformative actions. However, these actions are insufficient to reverse the crisis and achieve ecological integrity because they are non-holistic and based on human concerns and priorities. A more inclusive and integrative mindset is necessary for better-functioning circular processes. In this regard, this research presents a theoretical framework for an alternative circular design model – Toroidality – which is driven by collective knowledge and participatory action. Toroidality functions through the integrative capacity of collective knowledge and collaboration among human and non-human stakeholders in the ecosystem. Based on the intertwined cycles of collective knowledge and collective value-creation, Toroidality becomes a self-feeding circular design model. Through its four-phased circular design processes, Toroidality claims to generate solutions that have regenerative capacities. This article clarifies the conceptual background, theoretical framework and complementary notions to present the fundamentals of Toroidality. After this initial explanatory article, the dynamics of the phases and interactions among the stakeholders are aimed to be explored and reported in the following research, through a real-life case study.